Prevalence of active school transportation in the upper east and upper west regions of Ghana - Seidu Sofo; Eugene Asola; Emmanuel Thompson (International Journal of Public Health Science (IJPHS), 2019)
The use of active transportation such as walking to and from school is on the decline globally. The primary purpose of the study was to determine the prevalence of active school transportation among primary and junior high school students in the Upper East and Upper West regions of Ghana. The secondary purpose was to examine predictors for meeting the recommended daily number of steps. A total of 2505 (1117 boys and 1388 girls) primary (1583) and junior high school (922) students participated in the study. The distances from children’s homes to their schools, heights, and body weights were measured –their heights were used to estimate their stride lengths. The step count for each participant to and from school each day was calculated. Data were analyzed using conditional percentage distribution and Logit model. Analyses indicated that 98.96% of participants used active transportation to and from school. Over 63% of the students were within the normal BMI range. However, 26.47% of the participants were either thin or underweight while 9.9% were either overweight or obese. Overall, 46.47% of the participants met the recommended daily steps. The Logit model indicated that educational level, BMI, mode of transportation, region, height, and age were significant predictors for meeting the recommended daily number of steps. The prevalence of school active transportation in the present study was high compared to that reported in other studies. Furthermore, the prevalence of thinness and underweight were higher than in previous studies, while the prevalence in overweight and obesity were lower.